Single-Cell Transcriptome Analysis Reveals Inter-Tumor Heterogeneity in Bilateral Papillary Thyroid Carcinoma - Wang, Tiantian; Shi, Jinyuan; Li, Luchuan; Zhou, Xiaoming; Zhang, Hui; Zhang, Xiaofang; Wang, Yong; Liu, Lian; Sheng, Lei (Frontiers in Immunology, 2022)
Background The tumor microenvironment (TME) plays a pivotal role in cancer progression in papillary thyroid carcinoma (PTC), yet the composition and phenotype of cells within TME in bilateral PTCs are poorly understood. Methods We performed unbiased transcriptome-wide scRNA-seq analysis on 29,561 cells from 3 pairs of bilateral PTCs and 1 non-tumor thyroid sample. Analysis results were validated by a large-scale bulk transcriptomic dataset deposited in the TCGA database. Results Our integrative analysis of thyroid follicular cells revealed 42 signaling pathways enriched in malignant follicular cells, including cytokine-cytokine receptor interaction, PI3K-Akt signaling pathway, MAPK signaling pathway, and TNF signaling pathway. A 6-gene signature (CXCL3, CXCL1, IL1A, CCL5, TNFRSF12A, and IL18) in cytokine-cytokine receptor interaction pathway was constructed to predict the prognosis of patients with PTC, with high risk scores being associated with decreased overall survival (HR= 3.863, 95% CI = 2.233−6.682, P<0.001). Gene set variation analysis (GSVA) indicated pathways enriched in bilateral PTCs were significantly different, indicating great heterogeneity in bilateral PTCs, even with the same BRAF V600E mutation. Comprehensive analysis of T cells revealed that the proportion of CD8+ tissue-resident memory T cells expressing IFNG decreased in tumor samples with advanced N stage. Within the myeloid compartment, the ratio of suppressive M2-like to proinflammatory M1-like macrophages increased with advanced disease stage, which was confirmed in the bulk dataset using transcriptomic profiles. In addition, we also identified numerous biologically critical interactions among myeloid cells, T cells, and follicular cells, which were related to T cells recruitment, M2-like macrophage polarization, malignant follicular cells progression, and T cells inhibitory signaling. Conclusion Our integrative analyses revealed great inter-tumor heterogeneity within tumor microenvironment in bilateral PTCs, which will offer assistance for precise diagnosis and treatment.